Correlation between Neutrophil Gelatinase Associated with Lipocaline and Beta-2 Microglobulin with Other Renal Markers in Iraqi Patients with Multiple Myeloma - Inas Nazeeh Abed; Usama Salman Al-timari; Hiba Abid Al-Hussein hassan; Abbas Thamer Dwayyikh (Journal of Techniques)
Multiple myeloma, often known as myeloma, is a kind of bone marrow cancer. The bone marrow is a spongy tissue in the middle of some bones that creates the body's blood cells. The current study is designed to find the correlation between Neutrophil gelatinase-associated lipocalin and ß2-Microglobulin with other renal markers among patients with multiple myeloma and healthy people. One hundred twenty patients with multiple myeloma and sixty healthy control were attending the National Center for Teaching Laboratories (NCFTL), Baghdad Hospital Advisory (BHA), and Baghdad Teaching Hospital. For the period from November 2021 to March 2022. Information taken from patients involved age, genus, drugs used, and other medical details. Multiple myeloma disease was diagnosed using symptoms, biochemical testing, x-ray, and clinical examination by specialists. Then serum urea, creatinine, total protein, globulin, and albumin are done by Autoanalyzer. Furthermore, Neutrophil gelatinase-associated lipocalin and ß2-Microglobulin were done by ELISA technique. The present study found that the male patients in the age range (60-69) and (50-59) years had a higher percentage (30%, 20% and 36%,16.7%) than female patients in both studied groups. The multiple myeloma disease patients with urea and creatinine above normal had a highly significant increase (p= 0.000) in the mean ± SD of urea, creatinine, total protein, globulin, Beta 2 microglobulin, and Neutrophil gelatinase-associated lipocalin (57.83±30.92 mg/dl, 2.09±1.38 mg/dl, 77.95±13.08 g/l, 42.52±11.16 g/l, 39.14±16.20, 452.50±188.83) respectively. In addition, patients with urea and creatinine normal had a highly significant increase (p= 0.000) in the mean ± SD of creatinine, total protein, Globulin, Beta 2 microglobulin, and Neutrophil gelatinase-associated lipocalin (0.80±0.20 mg/dl, 73.07±11.75 g/l, 40.34±10.67 g/l, 43.28±18.78, 432.77±198.45) respectively compared with the healthy controls.